The Spectre of Communism: Aspects of Anti -Communist Propaganda in Post-Cold War Era (World Marxist Review, 2024)
“A SPECTRE is haunting Europe—the spectre of Communism. All the powers of old Eu rope have entered into a holy alliance to exorcise this spectre; Pope and Czar, Metternich and Guizot, French Radicals and German police-spies.” With this phrase, written in the beginning of the Manifesto of the Communist Party in 1848, Karl Marx and Friedrich Engels were pointing out the very first manifestation of the phenomenon of anti-communism.